Orientation-dependent recrystallization in an oxide dispersion strengthened steel after dynamic plastic deformation. Issue 1 (July 2015) - Zhang, Z B; Tao, N R; Mishin, O V; Pantleon, W
Abstract: The microstructure of the oxide dispersion strengthened ferritic steel PM2000 has been investigated after compression by dynamic plastic deformation to a strain of 2.1 and after subsequent annealing at 715 °C. Nanoscale lamellae, exhibiting a strong 〈100〉 + 〈111〉 duplex fibre texture, form during dynamic plastic deformation. Different boundary spacings and different stored energy densities for regions belonging to either of the two fibre texture components result in a quite heterogeneous deformation microstructure. Upon annealing, preferential recovery and preferential nucleation of recrystallization are found in the 〈111〉- oriented lamellae, which had a higher stored energy density in the as-deformed condition. In the course of recrystallization, the initial duplex fibre texture is replaced by a strong 〈111〉 fibre recrystallization texture.